Criminality in the age of ChatGPT: Analysis of the use of artificial intelligence as a criminal aggravating factor in Peru (Forseti. Law Review, 2025)
The author analyzes Law 32314, which incorporated the use of artificial intelligence and similarte chnologies as a criminal aggravating factor and specific modality in certain crimes. This article analyzes its legitimacy under the criteria of subsidiarity and necessity of punishment, and examines the institutional capacities required for effective implementation, as well as the benefits and risks of such a law.
Keywords: Artificial Intelligence; Criminal Aggravating Factors; Cybercrime; Deepfakes; Digital Evidence; Criminal Policy